Fatty acid profile, omegas and lipid quality in commercial cuts of pirarucu (Arapaima gigas Schinz, 1822) cultivated in excavated tanks - Cavali, Jucilene; Dantas Filho, Jerônimo Vieira; Nunes, Carla Taveira; Ferreira, Elvino; Pontuschka, Rute Bianchini; Zanella, Renato; Souza, Maria Luiza Rodrigues de (Acta Scientiarum. Animal Sciences, 2023)
The study aimed to determine the fatty acid profile, omegas and lipid quality indeces in commercial cuts of pirarucu (Arapaima gigas) of the slaughter class 11.1 to 14.0 kg. Sample collections were carried out in two fish processing industries located in Rondônia state, Brazil. The experimental design was completely randomized, with processing performed in triplicate. Data were submitted to ANOVA to assess differences between commercial cuts in chemical compositions. If ANOVA appeared statistically significant (α=0.05), the averages were compared by Tukey’s test. In the composition of fatty acids, there was a difference (p <0.05) between cuts. Commercial cuts that expressed the highest percentages of SFAs tail fillet 51.2%, of MUFAs fillet mignon 39.8% and of PUFAs deboned cut 20.7%. The indeces prescribed for lipid quality, ∑PUFAs/∑SFAs, ∑PUFAs (n-6/∑n-3), AI, TI and HH, indicate that commercial cuts have lipid quality. Deboned is the cut with the highest PUFA fatty acid content, with the highest values of Omega 3, 6, 7 and n-9 being also expressed. Nutritional information is important for the processes of conservation and processing, development of new products on the market, as well as guiding the form of preparation, thus providing commercial security for different market niches.